(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Despite the fact that investing in the Indian education industry is fraught with difficulties, it presents investors with several opportunities. A lot of research and publications show that the industry might provide substantial profits. The MHRD’s attempt to allow FEIs to establish autonomous bases in1India (without the requirement to partner1with Indian universities) appears to be a step toward enabling foreign engagement in India’s education industry. The purpose of this study is for the researcher to investigate Foreign Direct Investment (FDI) in Indian education in order to improve its influence on education. This study aims to analyse the potential for FDI to offer quality, greatness, and greater chances in "education." The research focuses on the benefits of FDI in education, with a special focus on India, and examines the benefits and drawbacks of FDI.